Upaya Mengatasi Perilaku Homoseksual di Lembaga Pendidikan Berbasis Pesantren - Lily Hidayati (Syamil: Jurnal Pendidikan dan Pemikiran Islam, 2026)
Homosexual behavior within the context of pesantren-based institutions in Indonesia poses significant challenges from both religious and social perspectives. This paper examines efforts to address homosexual behavior in pesantrens through the lens of contemporary fiqh, utilizing the arguments of the Qur'an, hadith, as well as social and customary legal norms. Homosexual behavior is one of the contemporary issues that draws attention across various aspects of life, including in the context of pesantren-based education in Indonesia. Using a qualitative approach and descriptive analysis, this study explores fiqh perspectives, psychological approaches, and educational interventions that can be applied. The results show that understanding social norms, along with a more inclusive approach, can be key to addressing this issue. Additionally, the importance of collaboration among religious scholars, educators, and parents in creating a supportive environment for students is emphasized.